Pengaruh Persepsi Kualitas Produk, Persepsi Harga dan Kepercayaan Merek Terhadap Keputusan Pembelian Ulang Smartphone Samsung Mahasiswa Universitas Negeri Padang - Suci Mulia Insyira; Agus Irianto (Jurnal Salingka Nagari, 2024)
This purpose of this study was to determine the effect of product quality perceptions, price perceptions and brand trust on Samsung smartphone repurchase decisions among Padang State University students. In determining the number of samples used the Slovin formula. With a total sample of 93 people taken using proportional random sampling technique. Data was obtained by distributing questionnaires to Padang State University students. The analytical method used is path analysis with SPSS version 25. The results of this study indicate that (1) there is a positive and significant influence between the perception of product quality on the decision to repurchase a Samsung smartphone, (2) there is a positive and significant influence between the perception of price on the decision Samsung smartphone repurchase, (3) there is a positive and significant influence between brand trust and Samsung smartphone repurchase decisions, (4) there is no influence between perceived product quality and repurchase decisions through brand trust, (5) there is no influence between perceived price on repurchase decisions through brand trust.